Disturbances in the IgG Antibody Profile in HIV-Exposed Uninfected Infants Associated with Maternal Factors - Rodrigo T. Camacho-Pacheco; Jessica Hernández-Pineda; Yesenia Brito-Pérez; Noemi Plazola-Camacho; Irma A. Coronado-Zarco; Gabriela Arreola-Ramírez; Mextli Y. Bermejo-Haro; M. Angel Najera-Hernández; Gabriela González-Pérez; Alma Herrera-Salazar; Andrea Olmos-Ortiz; Diana Soriano-Becerril; et al. (Journal of Immunology Research)
Over the last 20 years, the incidence of vertical HIV transmission has decreased from 25%–42% to less than 1%. Although there are no signs of infection, the health of HIV-exposed uninfected (HEU) infants is notoriously affected during the first months of life, with opportunistic infections being the most common disease. Some studies have reported effects on the vertical transfer of antibodies, but little is known about the subclass distribution of these antibodies. We proposed to evaluate the total IgG concentration and its subclasses in HIV+ mothers and HEU pairs and to determine which maternal factors condition their levels. In this study, plasma from 69 HEU newborns, their mothers, and 71 control pairs was quantified via immunoassays for each IgG isotype. Furthermore, we followed the antibody profile of HEUs throughout the first year of life. We showed that mothers present an antibody profile characterized by high concentrations of IgG1 and IgG3 but reduced IgG2, and HEU infants are born with an IgG subclass profile similar to that of their maternal pair. Interestingly, this passively transferred profile could remain influenced even during their own antibody production in HEU infants, depending on maternal conditions such as CD4+ T-cell counts and maternal antiretroviral treatment. Our findings indicate that HEU infants exhibit an altered IgG subclass profile influenced by maternal factors, potentially contributing to their increased susceptibility to infections.